The 79°N Glacier cavity modulates subglacial iron export to the NE Greenland Shelf - Stephan Krisch (Nature Portfolio, 2021)
A large fraction of ice sheet discharge enters the ocean subsurface from underneath large floating ice-tongues. Here the authors show that associated nutrient export may be governed by shelf circulation and, especially for Fe, particle-dissolved phase exchanges, which is largely independent from freshwater Fe content.